The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1159/000188935
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Hepatitis B Vaccine Use in Chronic Hemodialysis Patients

Abstract: The prevalence of hepatitis B virus (HBV) infection in our unit was 45% (86/190): there were 77 (40.5%) and 9 (4.7%) patients with previous and persistent HBV infection, respectively. Recombinant hepatitis B vaccine was given to 118 chronic HD patients with a regimen of 3 double doses administered intramuscularly at 0, 1 and 2 months, obtaining a seroprotection rate of 67% (79/118), 57% (45/79) being high responders. At month 24, 78% (40/51) maintained protective levels of anti-HBs, 45% (18/40) of them being h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 23 publications
(26 reference statements)
3
41
3
2
Order By: Relevance
“…Identical results were obtained by Kovacic et al [34]. No link between seroresponse rate and rHuEPO therapy, as assessed by rate of rHuEPO administration between responder and non-responder patients, was noted after the HBV vaccine schedule in another cohort study [35]. Liu et al [36] observed an increment of anti-HBs titers between the initial month and the seventh month, related to rHuEPO dosage, in the control group only.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Identical results were obtained by Kovacic et al [34]. No link between seroresponse rate and rHuEPO therapy, as assessed by rate of rHuEPO administration between responder and non-responder patients, was noted after the HBV vaccine schedule in another cohort study [35]. Liu et al [36] observed an increment of anti-HBs titers between the initial month and the seventh month, related to rHuEPO dosage, in the control group only.…”
Section: Discussionsupporting
confidence: 65%
“…Various approaches have been suggested in order to improve the response rate to hepatitis B vaccine in dialysis populations including increased vaccine doses [35] or shots, or intradermal vaccine route [38,39]. Higher immunogenicity has been observed when HBV vaccine has been given to CKD patients not yet requiring regular dialysis [19].…”
Section: Discussionmentioning
confidence: 99%
“…They have lower seroprotection rates compared with healthy subjects; moreover, after completion of vaccination schedule anti-HBs titers of responder uraemic patients are low and decline logarithmically over time (1). Various approaches have been made to overcome the non-responsiveness of chronic uraemic patients including co-administration of adjuvants (8), or immune modulators (9), intradermal administration of HB vaccine (10), increased vaccine doses, or additional inoculations (11). Alternatively, it has been recommended to start vaccination in the early stages of a renal disease (12), when one could anticipate that the primary immune response is still satisfactory.…”
Section: Contextmentioning
confidence: 99%
“…The standardized recommended (and even cost-effective) vaccination schedule for CKD or hemodialyzed patients consists of the intramuscular administration of 40 µg of recombinant vaccine (double the dose for the general population) at 0, 1, and 6 months [61]. The seroprotective titer of anti-HBs antibody is 10 IU/l.…”
Section: Hepatitis Bmentioning
confidence: 99%